2004
DOI: 10.1590/s1516-35982004000400007
|View full text |Cite
|
Sign up to set email alerts
|

Tempo de trânsito intestinal, desempenho, característica de carcaça e composição corporal de frangos de corte alimentados com rações isoenergéticas formuladas com diferentes níveis de óleo de soja

Abstract: RESUMO -Este estudo foi conduzido para avaliar o efeito da inclusão de 0,0; 3,3; 6,6 e 9,9% de óleo de soja em rações isoenergéticas sobre o tempo de trânsito (TT), desempenho, características de carcaça e composição corporal de frangos de Intestinal Transit Time, Performance, Carcass Characteristics and Body Composition in Broilers Fed Isoenergy Diets Formulated with Different Levels of Soybean OilABSTRACT -This study was conducted to evaluate the effect of 0.0, 3.3, 6.6, and 9.9% soybean oil inclusion in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
1
10

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 23 publications
(27 reference statements)
4
13
1
10
Order By: Relevance
“…Vet. Zootec., v.66, n.2, p.519-528, 2014 However, differently from the findings in this study, some researchers have demonstrated that the level of fat addition to the diet may cause variation in the chickens' abdominal fat content (Crespo and Esteve-Garcia, 2001;Andreotti et al, 2004a), as well as the saturation level of different lipid sources (Crespo and EsteveGarcia, 2001;Crespo and Esteve-Garcia, 2002;Villaverde et al, 2005;Wongsuthavas et al, 2008;Ferrini et al, 2008). According to Ferrini et al (2008), chickens fed polyunsaturated fatty acids presented a 30% reduction of abdominal fat when compared to chickens that had saturated fatty acids.…”
Section: Resultscontrasting
confidence: 59%
See 2 more Smart Citations
“…Vet. Zootec., v.66, n.2, p.519-528, 2014 However, differently from the findings in this study, some researchers have demonstrated that the level of fat addition to the diet may cause variation in the chickens' abdominal fat content (Crespo and Esteve-Garcia, 2001;Andreotti et al, 2004a), as well as the saturation level of different lipid sources (Crespo and EsteveGarcia, 2001;Crespo and Esteve-Garcia, 2002;Villaverde et al, 2005;Wongsuthavas et al, 2008;Ferrini et al, 2008). According to Ferrini et al (2008), chickens fed polyunsaturated fatty acids presented a 30% reduction of abdominal fat when compared to chickens that had saturated fatty acids.…”
Section: Resultscontrasting
confidence: 59%
“…These results are in accordance with other studies which showed that greater levels of oil added to feed benefit chickens' growth (Raber et al, 2009). Considering that the diets were isonutritive, the improvement of weight gain is due to the replacement of carbohydrate (starch) by fat, showing fat superiority in chickens' weight gain compared to carbohydrates, possibly improved by the increase of feed intake, consequently resulting in greater nutrient intake (Pucci et al, 2003;Andreotti et al, 2004a). Still, it is important to point out that oils and fats present lower caloric increase than carbohydrates during digestion, destining greater amounts of energy to maintenance and production demands.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another explanation for the lower feed intake of the hens fed 3100 kcal ME/kg was the high oil content of the feeds. Under these situations, feed passage from the gizzard to the duodenum is slower because the fat digestion in the duodenum is slow (Mateos & Sell, 1981;Mateos et al, 1982;Andreotti et al, 2004) because fats need to be emulsified, thereby reducing the appetite.…”
Section: Crude Protein and Metabolizable Energy Levels For Layers Reamentioning
confidence: 99%
“…In addition to physical and chemical factors related to lipids, the correct evaluation of their true energetic contribution becomes extremely difficult in birds due to the physiological difficulty they have in digesting and using them during the first few weeks of life (ANDREOTTI et al, 2004).…”
Section: Introductionmentioning
confidence: 99%